2014
DOI: 10.3934/mbe.2014.11.317
|View full text |Cite
|
Sign up to set email alerts
|

Modeling some properties of circadian rhythms

Abstract: Mathematical models have been very useful in biological research. From the interaction of biology and mathematics, new problems have emerged that have generated advances in the theory, suggested further experimental work and motivated plausible conjectures. From our perspective, it is absolutely necessary to incorporate modeling tools in the study of circadian rhythms and that without a solid mathematical framework a real understanding of them will not be possible. Our interest is to study the main process und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…62 For example, the emergence of phase-synchrony across large numbers of cells in circadian cooperative systems is the result of nonlinear coupling of oscillators across the cellular and multicellular levels. 63,64 Similarly, electrically phase-coupled systems in neuronal networks give rise to cooperative behaviors across large numbers of neurons. 65 The concept of biofield regulation offers a shift from a mechanical, chemistry-based view of biology to an information-based view.…”
Section: Biofield As a Conveyor Of Informationmentioning
confidence: 99%
“…62 For example, the emergence of phase-synchrony across large numbers of cells in circadian cooperative systems is the result of nonlinear coupling of oscillators across the cellular and multicellular levels. 63,64 Similarly, electrically phase-coupled systems in neuronal networks give rise to cooperative behaviors across large numbers of neurons. 65 The concept of biofield regulation offers a shift from a mechanical, chemistry-based view of biology to an information-based view.…”
Section: Biofield As a Conveyor Of Informationmentioning
confidence: 99%
“…An extremely large body of research has examined the conditions under which periodic behaviors, stochastic resonance (coherent entrainment due to noisy signals), and chaotic behaviors can occur in dynamical systems and systems of coupled oscillators, and the results have been applied to nearly every level of biological function, from the subcellular to the organismic 41 . For example, it has been clearly demonstrated that the generation of circa-dian rhythms at the suprachiasmatic nucleus is the result of the coupling of oscillators across the cellular and multicellular levels, 42 and a general framework for the emergence of synchronization in circadian cooperative systems employs non-linear coupled oscillators, resulting in phase-synchrony across large numbers of cells, 43 In neuronal networks, large scale simulations typically employ electrically phase-coupled systems that give rise to cooperative behaviors across large numbers of neurons 44 . Systems of genetic oscillators governing the synchronization of cells mediated by intercellular communication exhibit synchronous behaviors in spite of intrinsic parameter fluctuations and the presence of extrinsic noise 45 .…”
Section: Biological Clocks: Setting Life's Rhythmsmentioning
confidence: 99%